Dominant Factor Affecting to Intention of Nursing Students toward Basic Life Support (BLS) Effort: Using Theory of Planned Behavior Approach - Yusron Amin; Haswita (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The less intention of nursing students toward Basic Life Support (BLS) effort could affect less quality of basic life support performed by nursing students. The study aimed to analyze the dominant factor affecting the intention of nursing students toward basic life effort using the theory of planned behavior approach. The samples were 100 respondents who met inclusion criteria using the purposive sampling technique. The instrument was a self-administered questionnaire that consisted of the variables from the theory of planned behavior. The data analysis using logistic regression. The result showed that attitude was the dominant factor affecting to intention (p=0.000; OR=47.175). followed by subjective norm (p=0.011; OR=19.002) and perceived behavioral control (PBC) (p=2.344; OR=10.428). Nursing students' intention could be optimized through the effort to enhance attitude toward basic life support. enhancing external support (supervisors and nursing student peers). and enhancing perception about the function of self-control to utilize the resources (perceived behavioral control).